On the flow behaviour of 2D flexible airfoils - Huang, Yu Hao (2018)
This thesis studies the on flow behaviour of the corrugated airfoil proposed by B. G Newman et al. [1]. Unlike previous studies by Flint et al. [2], this study put the flexibility and deformation of the airfoil into consideration. As the wings of real life dragonfly wings are flexible in nature, it is only natural to consider the airfoils used in fluid dynamic calculations as flexible in order to better understand how insects such as dragonfly can achieve better flight dynamics at low Reynold’s number with their wings. The aim of this study is to study the lift and drag of the airfoil, the pressure distribution around, and streamline across the flexible airfoil at different angle of attacks. A computational fluid dynamics programme was set up and a flexible airfoil was placed in a low speed fluid flow at 11 different angles of attack. A stiff airfoil with identical dimensions was placed in the exact same setting for control purpose. The lift coefficient of the flexible airfoil was found to be lower than that of the stiff airfoil but the stall angle increased and stall was delayed. The drag coefficient of flexible airfoil was also lower than the stiff airfoil and the lift over drag ratio for the flexible airfoil was lower compared to the stiff airfoil at higher angles of attack.